Content Creator Legal Protection of The Copyrights of Content Reuploaded by Other Parties for Commercial Purposes - Fayola, Carissa; Sitompul, Roswita; Isnainul, OK (International Journal of Business, Law, and Education, 2024)
In the current era of globalization, technological advancements are rapidly progressing, especially in the field of information technology, giving rise to the phenomenon of "creators." Creators are individuals or groups who produce creative content, such as videos, photos, or other digital forms, accessible via the internet. This profession demands protection for the Intellectual Property Rights (IPR) generated by creators. This protection is crucial because content uploaded without permission can economically and morally harm the creators. Unauthorized re-uploading creates serious problems for creators, damaging their image and credibility. It also leads to economic losses as creators lose potential income from affiliate links. Copyright, as regulated by Law Number 28 of 2014, provides legal protection for creators, covering both moral and economic rights over their works. This study aims to analyze the impact on the image and economic rights of creators, the factors hindering law enforcement, and the legal efforts made to address copyright violations. The research uses a normative juridical approach with secondary data analysis from written and electronic sources. The results of this study indicate that the government has implemented various measures to protect the copyright of content creators from violations, especially by unauthorized reuploaders. These measures include supervising the content upload process, ensuring content quality meets standards, and monitoring content usage to prevent misuse. The government has also developed secure information systems, monitored user activities, and enforced legal sanctions against copyright violators. The government is expected to strengthen regulations and IPR protection and enhance monitoring of unauthorized content re-uploading.